Exploring the impacts of distance higher education on adult learners’ lives and reclaiming lifelong learning as a human development process - Claudia Neves; Susana Henriques (Open Praxis, 2020)
This article intends to launch discussion and reflection on two main themes: lifelong learning and digital literacy in nowadays societies. In looking for the intersections between these concepts to connote them with a more humanistic and holistic perspective, we explore the potentials of distance learning in the lives of adult learners. The empirical basis for this exploration is a survey applied to 706 (143 respondents) graduates in the education of the Portuguese Open University to know their future projects and the impact of this degree in the various dimensions of their personal, social and professional lives. The conclusions of this analysis point to recognition, by the respondents, of the positive impacts that distance higher education has in their personal and social lives. However, these impacts are not as visible in professional terms since the answers show little significant professional progressions. In this sense, the article concludes that it is important to rethink the founding ideas of the concept of lifelong learning from a humanistic perspective and to approach it with a holistic and transversal conception of what is now defined as digital literacy. Distance education, for adult learners, is a scenario that not only strengthens the personal, social and professional development of individuals, but also the development of competencies applied not only to the digital world but also to each person’s daily activities.